Differences in Radiological Risk Perceptions Following Online and In-Person Workshops - Victoria B. Strait; Robert H. Hayes; Mohammad G. Mostofa (Health Physics, 2026)
Nuclear energy is widely regarded as a critical part of the pathway toward a secure, low-carbon electricity grid, yet long-term management of used nuclear fuel remains a persistent challenge. Although technically viable options for interim and consolidated storage exist, public concern and community opposition — rooted in historical distrust and risk perception — continue to complicate siting decisions. In response, recent federal efforts have emphasized collaboration-based approaches and community engagement, though empirical evidence on the effectiveness of different engagement strategies remains limited. This study examines how the structure and delivery of community engagement influence changes in public attitudes toward hosting interim used nuclear fuel storage facilities. Using survey data from 13 educational workshops around the United States, we evaluate: (1) the inclusion of trust-building content prior to technical content, and (2) engagement format, comparing online and in-person workshops. Analyses focus on participant changes in perceptions of safety, risk, and support for hosting, using the Wilcoxon rank-sum test and other non-parametric hypothesis tests on surveys conducted before and after workshops. Results indicate that workshop participation is associated with some measurable attitude changes, with significant (p < 0.05) differences in response variability for some questions across workshop formats. In particular, when comparing nuclear energy to other clean energy sources, in-person workshop participants are substantially more likely to gain a more favorable opinion of nuclear energy than online participants. These findings contribute empirical evidence on how trust-building and delivery mode shape outcomes in public engagement on complex and contested energy policy issues such as storage of used nuclear fuel.